Considerations on the common regulatory issues among the IMO instruments for realization of maritime autonomous surface ships. Issue 1 (November 2020) - Shiokari, M; Ota, S
Abstract: The Maritime Safety Committee (MSC) of the International Maritime Organization (IMO) included an agenda item "Regulatory Scoping Exercise (RSE) for the use of Maritime Autonomous Surface Ships (MASS)" in order to determine how the safe, secure and environmentally sound operation of MASS may be introduced in the regulations. The results of the RSE have been reported to the MSC, and they will be discussed in the 102th session. The purpose of this study is to provide suggestions for making decisions on the necessary future work at the MSC. The authors have reviewed all the results of the RSE under the purview of the MSC and made discussions on the ways of addressing some important common issues. The suitability of the specific ways of addressing these issues may be turned out in the actual works for amendments. On the other hand, regarding the priority of the discussions, the authors consider that it is appropriate to give priority to the discussions on the partial automation and remote operation with seafarers on board over the fully autonomous or remote operations without seafarers on board. Also, it seems appropriate to give priority to the discussions on the navigation systems and tasks.